The impact of parents' physical activity goals and parental attitudes on physical activity during leisure time among children in middle childhood - Kamionka, Agata; Lipowska, Małgorzata; Lizińczyk, Sebastian; Lipowski, Mariusz (Frontiers in Public Health, 2023)
Introduction Parents' supportiveness and health-promoting habits significantly affect the intensity of children's physical activity (PA) and the involvement of parents in their engagement in PA; in this domain, both the hours devoted to PA and PA goals can be assessed. The family plays an important role in shaping the physical and social organization of the environment for children aged 4–6 years. Methods A total of 680 families with 5-year-old children (330 girls, 350 boys) took part in the study. Data were collected from these participants, who were recruited from preschools and primary schools in the Pomeranian region of Poland. The aim of this study was to determine whether the involvement of parents in PA mediates the influence of parental attitudes on the ways in which their children spend their leisure time. Results The results showed that not all parental attitudes had direct impact on children's leisure time in PA and outside PA. Other aspects parental attitude had no significant impact on offspring's free time. Among fathers, only four aspects of parental attitude (namely, acceptance–rejection, inconsistency, autonomy, and overprotectiveness) had an impact on PA goals. Mothers' goals were influenced by the strength of a larger number of aspects of attitude (namely, acceptance–rejection, autonomy, inconsistency, over-demandingness, and overprotectiveness). Similarly, the strength of mothers' and fathers' acceptance–rejection attitudes, attitudes of autonomy, and overprotectiveness had an impact on their PA goals but were not directly linked to their children's leisure-time engagement in PA. Discussion Not all parental attitudes have a direct impact on children's PA or non-PA leisure time. However, the goals of PA parents have been recognized influence the leisure time of children in PA and outside PA. The most statistically significant relationship for both mothers and fathers was between parental attitudes and PA goals. Parental attitudes do not play a significant role in explaining involvement in PA or lack of it in leisure time among 5-year-old children.